Thermal characterization of solid lipid nanoparticles containing praziquantel - de Almeida, Adelia Emilia [UNESP]; Ribeiro Souza, Ana Luiza [UNESP]; Cassimiro, Douglas Lopes [UNESP]; Daflon Gremiao, Maria Palmira [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer, 2012)
Solid lipid nanoparticles (SLNs), loaded and unloaded with praziquantel (PRZ-load SLN and PRZ-unload SLN) were prepared by two different procedures: (a) oil-in-water hot microemulsion method, obtaining at 70 degrees C an optically transparent blend composed of surfactant, co-surfactant, and water; and (b) oil-in-water microemulsion method, dissolving the lipid in an immiscible organic solvent, emulsified in water containing surfactants and co-surfactant, and then evaporated under reduced pressure at 50 degrees C. The mean diameter, polydispersity index (PdI), and zeta potential were 187 to 665 nm, 0.300 to 0.655, and -25 to -28 mV respectively, depending on the preparation method. The components, binary mixture, SLNs loaded and unloaded with PRZ, and physical mixture were evaluated by differential scanning calorimetry (DSC) and thermogravimetry (TG). The non-isothermal isoconversional Flynn-Wall-Ozawa method was used to determine the kinetic parameters associated with the thermal decomposition of the samples. The experimental data indicated a linear relationship between the apparent activation energy E and the pre-exponential factor A, also called the kinetic compensation effect (KCE), allowing us to determine the stability with respect to the preparation method. Loading with PRZ increased the thermal stability of the SLNs.
Keywords: Solid lipid nanoparticles; SLN; Kinetic compensation effects; Praziquantel; Nonisothermal kinetics